Efficacy of extended aromatase inhibitors for hormone-receptor–positive breast cancer: A literature-based meta-analysis of randomized trials. (August 2019) - Corona, S.P.; Roviello, G.; Strina, C.; Milani, M.; Madaro, S.; Zanoni, D.; Allevi, G.; Aguggini, S.; Cappelletti, M.R.; Francaviglia, M.; Azzini, C.; Cocconi, A.; et al.
Abstract: Background: Endocrine treatment with Tamoxifen and aromatase inhibitors (AIs) is a staple in the management of hormone receptor positive breast cancer (HR + BC). It has become clear that HR + BC carries a consistent risk of relapse up to 15 years post-diagnosis. While increasing evidence supports the use of extended adjuvant Tamoxifen over 5 years, controversial data are available on the optimal duration of extended AIs adjuvant treatment. We performed a meta-analysis to assess the real impact of extended adjuvant therapy with AIs on disease-free survival (DFS). Methods: A literature-based meta-analysis of randomized controlled trials (RCTs) was undertaken. Relevant publications from PubMed, the Cochrane Library, and abstracts from American Society of Clinical Oncology (ASCO) and San Antonio Breast Cancer (SABCS) symposia were searched. Primary and secondary endpoints were Disease Free Survival (DFS) and overall survival (OS) respectively. A subgroup analysis was also performed to elucidate the impact of nodal involvement. Results: The pooled analysis revealed a significant increase in DFS in the extended AIs group (hazard ratio (HR): 0.78, 95% CI: 0.68–0.90; P = 0.0006). The subgroup analysis according to nodal status showed a greater DFS benefit with extended AIs in patients with positive nodes (HR = 0.67 versus 0.80). Our analysis also demonstrated no improvement in OS with extended AIs (HR = 0.99, 95%CI: 0.87–1.12; P = 0.84). Conclusion: This work confirmed the efficacy of extended adjuvant treatment with AIs for HR + early breast cancer, with a 22% increase in DFS, but no impact on OS. Greater efficacy was observed in women with positive nodal status. Highlights: Adjuvant endocrine therapy reduces the risk of recurrence and increases survival rates in breast cancer patients. The benefit of extended adjuvant endocrine therapy with aromatase inhibitors (AIs) is currently being debated. Our retrospective analysis of 8 randomized clinical trials provides evidence of a disease free survival (DFS) benefit with extended adjuvant AIs therapy. DFS benefit was higher in patients with positive nodal status. Identification of new biomarkers could help identify specific subgroups of patients able to benefit from extended adjuvant endocrine therapy with AIs.